Effects of ARB or ACE-Inhibitor Administration on Plasma Levels of Aldosterone and Adiponectin in Hypertension - Kawachi, Kenji; Iwasaki, Tsutomu; Hoshino, Jin; Morishita, Koujurou; Ohyama, Yoshio; Nakamura, Tetsuya; Saito, Tomoko; Saito, Yuichiro; Kurabayashi, Masahiko; Hosoi, Tsutomu (International Heart Journal, 2009)
Aldosterone production causes vascular injury and may occur despite the long-term administration of angiotensin converting enzyme-inhibitors (ACE-I) (ie, aldosterone breakthrough). The angiotensin II receptor blocker (ARB) telmisartan can function as a ligand for peroxisome proliferator-activated receptor (PPAR) γ. Stimulation of PPAR γ has been demonstrated to raise adiponectin production and suppress angiotensin II type 1 receptor expression. Thus, we investigated the effect of the ACE-I perindopril erbumin (perindopril) and the ARB telmisartan on plasma levels of aldosterone and adiponectin. Patients with essential hypertension were randomly assigned to receive 48 weeks of perindopril (2-8 mg/d) or telmisartan (20-80 mg/d). We measured adiponectin, aldosterone, angiotensin II, and renin at weeks 0, 8, 24, and 48. A total of 53 subjects were randomized. Data on 51 subjects (25 in the perindopril group and 26 in the telmisartan group; mean age, 65.1 years) were available for analyses. Plasma aldosterone decreased significantly in both the telmisartan (69.9 ± 5.6 to 58.1 ± 5.4 pg/mL) and perindopril (74.1 ± 4.7 to 64.7 ± 5.3 pg/mL) groups at 8 weeks, but returned toward the baseline in the perindopril group (67.9 ± 4.1 pg/mL) at 24 weeks. Plasma glycated hemoglobin levels or urine albumin did not change significantly after the treatment in either group. Telmisartan seemed to be more effective at suppressing aldosterone and raising adiponectin levels than perindopril; however, improvements in insulin sensitivity and albuminuria were not detected. These results are consistent with the idea that the use of an ARB with PPAR γ stimulating activity is equivalent to ACE-I for the treatment of hypertension.